1993
DOI: 10.1161/01.res.72.4.901
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of regional contractile function and oxidative metabolism in stunned myocardium induced by 1-hour circumflex coronary artery stenosis in chronically instrumented dogs.

Abstract: Stunned myocardium produced by 1 hour of critical coronary artery stenosis was evaluated for alteration in regional mechanical function and overall oxidative and fatty acid metabolism by positron emission tomography (PET) in chronically instrumented dogs. Twenty-seven dogs, chronically instrumented for measurements of left ventricular pressure and regional myocardial wall thickening in normal and ischemic zones, were subjected to a 1-hour period of myocardial ischemia produced by graded left circumflex coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…[2][3][4][5][6] Slow recovery of the tracer uptake after ischemic insult has been found in both clinical and experimental studies. [17][18][19] In the present study, the reduced tracer uptake by the IR seen in the early image after tracer injection was not present in the delayed image because of slow clearance of the tracer in the IR, a finding consistent with the previous study. 10 Beta-adrenoceptor blockers, including carvedilol, are frequently prescribed for patients with coronary heart disease and heart failure, so it is important to clarify their influence on the distribution and intracellular metabolism of FA tracers in the myocardium.…”
Section: Effects Of -Adrenoceptor Blockade On Cardiac Fa Imagingsupporting
confidence: 92%
“…[2][3][4][5][6] Slow recovery of the tracer uptake after ischemic insult has been found in both clinical and experimental studies. [17][18][19] In the present study, the reduced tracer uptake by the IR seen in the early image after tracer injection was not present in the delayed image because of slow clearance of the tracer in the IR, a finding consistent with the previous study. 10 Beta-adrenoceptor blockers, including carvedilol, are frequently prescribed for patients with coronary heart disease and heart failure, so it is important to clarify their influence on the distribution and intracellular metabolism of FA tracers in the myocardium.…”
Section: Effects Of -Adrenoceptor Blockade On Cardiac Fa Imagingsupporting
confidence: 92%
“…Weinheimer et al observed that preservation of 11 C-acetate clearance after 1 week and the recovery of wall motion after 4 weeks were significantly correlated in dogs after a 1-or 4-h occlusion of the LAD [63]. Similar observations were reported by Heyndrickx et al after a 1-h occlusion of the circumflex artery in dogs [64].…”
Section: Acetate Clearance In (Post-)ischaemic Myocardium In Animalssupporting
confidence: 59%
“…Examination during the chronic stage, however, has disclosed the improvement of the decreased tracer uptake in the 123 I-BMIPP and 11 C-palmitic acid PET imaging, and that 18 F-FDG PET imaging showed a decreased tracer uptake. 14,15 These findings show that it is not aerobic glucose metabolism but fatty acid metabolism that mainly produces the energy during the chronic stage.…”
Section: Discussionmentioning
confidence: 98%
“…Examination of stunned myocardium in the subacute stage has revealed that 123 I-BMIPP myocardial imaging and 11 Cpalmitic acid with positron emission tomography (PET), which is considered to be an accurate agent for the quantification of regional fatty acid utilization, decreased the tracer uptake, and 18 F-fluorodeoxyglucose (FDG) PET imaging demonstrated an increased tracer uptake. 14,15 This indicates that it is not fatty acid metabolism but aerobic glucose metabolism that mainly produces the energy in the myocardium during the subacute stage. Examination during the chronic stage, however, has disclosed the improvement of the decreased tracer uptake in the 123 I-BMIPP and 11 C-palmitic acid PET imaging, and that 18 F-FDG PET imaging showed a decreased tracer uptake.…”
Section: Discussionmentioning
confidence: 99%